2022
DOI: 10.1111/jbi.14314
|View full text |Cite
|
Sign up to set email alerts
|

Variable vulnerability to climate change in New Zealand lizards

Abstract: Aim:The primary drivers of species and population extirpations have been habitat loss, overexploitation and invasive species, but human-mediated climate change is expected to be a major driver in future. To minimise biodiversity loss, conservation managers should identify species vulnerable to climate change and prioritise their protection. Here, we estimate climatic suitability for two species-rich taxonomic groups, then use phylogenetic analyses to assess vulnerability to climate change.Location: Aotearoa Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…However, the long-term consequences of increased climate heating (including the potential for harmful extremes of temperature) on activity timing, increase in winter rainfall and other important aspects of natural history including maternal gestation length and offspring phenotypic traits, remain unclear. Recent finding suggested that lizards at higher elevation will experience greater impact of climate change due to decrease in habitat availability especially for our study species ( Jarvie et al, 2022 ); but consequences of increased warming may not be enormous when microclimate properties and lizards’ biology are considered ( Chukwuka et al, 2021 ). In addition, the potential for increased vulnerability to predation while emerging ( Wilson and Cooke, 2004 ; Sperry et al, 2010 ), including from introduced mammals, which themselves will be impacted by climate change, will be important to address.…”
Section: Discussionmentioning
confidence: 99%
“…However, the long-term consequences of increased climate heating (including the potential for harmful extremes of temperature) on activity timing, increase in winter rainfall and other important aspects of natural history including maternal gestation length and offspring phenotypic traits, remain unclear. Recent finding suggested that lizards at higher elevation will experience greater impact of climate change due to decrease in habitat availability especially for our study species ( Jarvie et al, 2022 ); but consequences of increased warming may not be enormous when microclimate properties and lizards’ biology are considered ( Chukwuka et al, 2021 ). In addition, the potential for increased vulnerability to predation while emerging ( Wilson and Cooke, 2004 ; Sperry et al, 2010 ), including from introduced mammals, which themselves will be impacted by climate change, will be important to address.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies suggested that the tuned MaxEnt models can perform comparably to ensemble SDMs (Hao et al, 2020 ; Low et al, 2021 ). To improve the performance of MaxEnt and avoid overfitting, following Jarvie et al ( 2021 ), we ran 24 Maxent models based on all possible combinations of eight regularization multipliers (i.e., 0.5, 1, 1.5, 2, 2.5, 3, 3.5, and 4) and three feature class options (i.e., linear, linear/quadratic, and linear/quadratic/product). The performance of each model was evaluated using a non‐spatial fivefold cross‐validation.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, recent studies suggest that the interacting effects of climate and land‐use change are complex and species‐specific, for they could either amplify or buffer the isolated impact of a single factor for a certain species (Auffret & Thomas, 2019 ; Radinger et al, 2016 ). Therefore, to avoid further biodiversity loss, conservationists need to identify species likely to be vulnerable to global change, which requires improved estimations of species' range shifts under the combination of climate and land use change scenarios (Jarvie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to avoid further biodiversity loss, conservationists need to identify species likely to be vulnerable to global change, which requires improved estimations of species' range shifts under the combination of climate and land use change scenarios (Jarvie et al, 2022).…”
mentioning
confidence: 99%